Pengembangan Sistem Informasi Manajer Suku Cadang Sepeda Motor Berbasis Web di Bengkel Benny Motor - Nugroho Wisnu Murti; Diki Wiliandi; Rasyid Dwi Saputra; Wasis Haryono (Journal of Artificial Intelligence and Innovative Applications (JOAIIA), 2020)
Benny Motor Workshop is a trading unit which is engaged in selling motorcycle spare parts and providing motorcycle servicing services. Where this trading unit must meet the needs of consumers every day, so sales are the main thing in the company.Along with the development of information technology, Benny Motor Workshop needs to utilize information technology to improve performance and productivity in order to survive and compete in its business. Benny Motor Workshop has a lot of goods, but the data collection is often done errors in the calculation of the entry and exit of spare parts, this is because the data collection system is still manual.In purchasing data processing, spare part stock and Benny Motor workshop spare part sales are recorded in a notebook, this makes data processing inefficient and often appears like the loss of spare parts purchase invoices and spare parts sales invoices which are proof evidence of the transaction. In this case a web-based motorcycle spare parts management information system is needed as a solution to the problems that exist in the Benny Motor workshop.